A Bottom-Up Approach to Understanding Low-Income Patients: Implications for Health-Related Policy. Issue 3 (September 2018) - Viswanathan, Madhu; Duncan, Ronald; Grigortsuk, Maria; Sreekumar, Arun
A bottom-up approach grounded in micro-level understanding of the thinking, feeling, behavioral, and social aspects of living with low income and associated low literacy can lead to greater understanding and improvement of interactions in the health arena. This paper draws on what we have learned about marketplace interactions in subsistence economies to inform innovations in medical education, design and delivery of healthcare for lowincome patients, outreach education, and future micro-level research at the human-healthcare interface.